Edge creation changes the timing and intensity of phenological reproductive patterns and species activities in forest tree communities - Elias,João Pedro Costa (2021)
Abstract Environmental characteristics are among the most important triggers and regulators of plant phenophases, so that the abiotic and biotic changes driven by habitat loss and fragmentation can result in alterations of plant phenological patterns. We investigated whether forest edge and interior have differences in phenological pattern of tree communities. We followed the reproductive phenologies of tree communities in seven forest fragments on a monthly basis for two years (in 200 m² edge and interior plots per fragment). We sampled a total of 0.28 ha of anthropic forest fragments, comprising 313 trees (180 in edge, 133 in interior) belonging to 103 species and 34 families. Our results evidenced reproductive phenological changes between edge and interior tree communities, with: (i) phenological activities differing temporally between the two habitats (edge and forest interior) in all tree communities; (ii) greater phenological intensity at the forest edge than in the forest interior among tree species common to both habitats; (iii) more tree species showed phenological activity at the forest edge in 2010 and interior in 2011, when considering only those exclusive to each habitat. Habitat fragmentation can therefore alter microenvironmental characteristics and influence biologic processes, including the reproductive phenologies of trees, through edge formation.